DESCRIPTION OF BLOOD SUGAR LEVELS OF DM PATIENTS WITH ORAL HYPOGLYCEMIC DRUG ADMINISTRATION AT ONE OF THE JEMBER HOSPITALS - Khafifah Al Addawiah (LPPM Universitas dr. Soebandi, 2024)
Background: Diabetes Mellitus (DM) is a chronic disease caused by impaired metabolism of fat, carbohydrates and proteins, characterized by high blood sugar levels that exceed normal limits. The incidence of DM will increase every year, the increasing incidence of DM can be caused by risk factors, such as obesity, physical activity and age. This study aims to determine the use of metformin and glimepiride along with a picture of blood sugar levels of diabetes mellitus patients before and after administering single metformin and glimepiride drugs at one of the hospitals in Jember. Methods: This study includes non-experimental research, namely obervasional with analytical descriptive research design with cross sectional methods. Samples were taken using a total sampling technique that met the inclusion criteria of 32 outpatients. Data were taken using observation sheets and recapitulation sheets. Research Results: The use of metformin and glimepiride drugs in type 2 DM patients in one of the hospitals in Jember is metformin as much as 15.6% while glimepiride is 84.4%. The data showed the difference in the average blood sugar levels of patients before using metformin which was 233.2 mg / dl and after using metformin which was 168.4 mg / dl and the difference in the average blood sugar levels of patients before using glimepiride was 246.7 mg / dl and after using glimepiride was 181.5 mg / dl. Conclusion: The use of metformin and glimepiride alone drugs in patients with type 2 diabetes showed that almost all patients used a single glimepiride drug which was 84.4%. Single metformin and glimepiride drugs were also able to lower blood sugar levels of type 2 diabetes patients in one of the medical record rooms of the outpatient hospital installation in Jember.